2015
DOI: 10.4194/1303-2712-v15_1_11
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In this study, the total lipid, total protein and fatty acid compositions of Capoetaangorae were investigated. Total lipid content ratios (as wet weight) were found to be as 1.44% in spring, 6.41% in summer, 4.25% in autumn and 4.29% in winter. Total protein ratios in the muscle of C. angorae also varied from16.55% to19.24% during the year. The major fatty acids in the muscles of both sexes were palmitic, oleic, palmitoleic, eicosapentaenoic and docosahexaenoicacids. The proportions of n3 PUFAs were higher tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…This relationship could be used to predict the water content from fat or protein content of the processed catfish [11]. However, proximate composition of fish differs from species to species, individual to individual, considering size, sex, season, feeding, and processing stress [18][19][20][21]. Many studies have reported channel catfish baseline proximate composition [22][23][24], while data for hybrid catfish proximate composition in the process lines are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…This relationship could be used to predict the water content from fat or protein content of the processed catfish [11]. However, proximate composition of fish differs from species to species, individual to individual, considering size, sex, season, feeding, and processing stress [18][19][20][21]. Many studies have reported channel catfish baseline proximate composition [22][23][24], while data for hybrid catfish proximate composition in the process lines are scarce.…”
Section: Introductionmentioning
confidence: 99%